Preparation method of phosphotungstic acid coated nickel-rich ternary lithium ion battery positive electrode material and preparation method of phosphotungstic acid coated nickel-rich ternary lithium ion battery positive electrode material

By coating phosphotungstic acid on the positive electrode material of nickel-rich ternary lithium-ion battery, the problem of poor structural instability and thermal stability in the long-term cycle is solved, and high specific capacity, low thermal yield and good thermal safety are achieved. Performance battery.

CN119297249AActive Publication Date: 2025-01-10CHANGZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411499703.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-10
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

During the long cycle of nickel-rich ternary lithium-ion battery positive electrode material, there is structural reconstruction, particle rupture, transition metal ion dissolution and high deliquefaction, resulting in poor thermal stability of the oxide positive electrode, which is easy to decompose at high temperature to produce oxygen, resulting in fires. and explosion accident.

Method used

The positive electrode material of nickel-rich ternary lithium-ion battery is coated with phosphotungstic acid. By mixing the nickel-cobalt-manganese precursor with a lithium source and sintering it, it forms a phosphotungstic acid clad layer, which improves the specific capacity of the material, low thermal yield and Security.

Benefits of technology

It significantly improves the discharge capacity and charge and discharge stability of the battery, extends the battery life, reduces the heat production rate and heat production, and enhances the thermal safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297249A_ABST
    Figure CN119297249A_ABST
Patent Text Reader

Abstract

The invention discloses a phosphotungstic acid coated nickel-rich ternary lithium ion battery positive electrode material, which comprises a nickel-rich ternary lithium ion battery positive electrode material and a surface coating material phosphotungstic acid, and the nickel-rich ternary lithium ion battery positive electrode material is composed of a nickel cobalt manganese hydroxide precursor and a lithium source. The invention also discloses a preparation method of the phosphotungstic acid coated nickel-rich ternary lithium ion battery positive electrode material, which comprises the following steps: mixing a nickel cobalt manganese oxide precursor and a lithium source, continuously grinding, fully mixing and sintering to obtain the nickel-rich ternary lithium ion battery positive electrode material, mixing the nickel-rich ternary lithium ion battery positive electrode material with phosphotungstic acid, continuously grinding, and drying to obtain the phosphotungstic acid coated nickel-rich ternary lithium ion battery positive electrode material. And fully mixing and sintering to prepare the phosphotungstic acid coated nickel-rich ternary lithium ion battery positive electrode material. The phosphotungstic acid coated nickel-rich ternary lithium ion battery positive electrode material is low in cost, high in stability, low in heat production rate and low in heat production, the prepared battery is high in specific capacity, the service life of the battery is effectively prolonged, and the safety of the battery is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a phosphotungstic acid coated nickel-rich ternary lithium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] As the global demand for clean energy and sustainable transportation continues to grow, the electric vehicle market is rising rapidly. Traditional lithium-ion battery cathode materials use lithium cobalt oxide, etc., but the scarcity and high cost of cobalt resources limit their development in large-scale applications. Nickel-rich ternary lithium-ion battery cathode materials have gradually become a research hotspot and development direction of lithium-ion battery cathode materials due to their high specific capacity, relatively low cost and good safety.

[0003] As the nickel content in nickel-rich ternary lithium-ion battery cathode materials increases, the stability of the material decreases, and structural reconstruction, particle rupture, transition metal ion dissolution, and cathode-electrolyte interface film damage are prone to occur during long-term cycling. The oxide cathode in a highly delithiation state has extremely poor thermal stability and is easily decomposed to produce oxygen at high temperatures, causing severe oxidation of the electrolyte on the cathode surface, releasing a large amount of heat and producing a large amount of gas, which can cause serious fire and explosion accidents in the battery in severe cases.

[0004] The above problems need to be solved urgently, so it is necessary to develop a phosphotungstic acid-coated nickel-rich ternary lithium-ion battery positive electrode material and a preparation method thereof. Summary of the invention

[0005] In view of the shortcomings of the prior art, an object of the present invention is to provide a phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material, firstly, a nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 The nickel-rich ternary lithium-ion battery positive electrode material is prepared by mixing (OH)2) with a lithium source, and then the nickel-rich ternary lithium-ion battery positive electrode material and phosphotungstic acid are sintered in a tubular furnace to obtain a phosphotungstic acid-coated nickel-rich ternary lithium-ion battery positive electrode material with high specific capacity, low heat generation rate and high safety.

[0006] To achieve the above technical problems, the present invention provides the following technical solutions:

[0007] A phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material, comprising a nickel-rich ternary lithium-ion battery positive electrode material and a material coated on its surface, phosphotungstic acid (H3O 40 PW 12 ·χH2O), the positive electrode material of nickel-rich ternary lithium-ion battery is composed of nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn0.05 (OH)2) and a lithium source.

[0008] Preferably, the mass ratio of each component of the nickel-rich ternary lithium-ion battery positive electrode material is: nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 (OH)2):lithium source is 1:1.05.

[0009] Preferably, the phosphotungstic acid (H3O 40 PW 12 ·χH2O) is 0.5% to 2%.

[0010] Preferably, the lithium source is one of lithium hydroxide (LiOH·H2O) and lithium carbonate (Li2CO3).

[0011] Preferably, the nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 The particle size of (OH)2) is selected from one or more of 25 μm, 50 μm, 100 μm, 200 μm, 400 μm.

[0012] Another object of the present invention is to provide a method for preparing the above-mentioned phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material, which specifically comprises the following steps:

[0013] Step 1: Weigh the nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 (OH)2) 10 parts and lithium source 10.5 parts;

[0014] Step 2: weigh the nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 (OH)2) and lithium source were mixed and ground for 30 min;

[0015] Step 3: Place the fully mixed materials into a tube furnace and sinter at 500°C for 5 hours with an oxygen flow rate of 50-150 ml / min;

[0016] Step 4: Take out the cooled powder and grind it for 5 minutes;

[0017] Step 5: placing the ground material into a tube furnace and sintering at 680-760° C. for 15 hours to obtain the nickel-rich ternary lithium-ion battery positive electrode material;

[0018] Step 6: Weigh 0.5% to 2% of the mass of the synthesized nickel-rich ternary lithium-ion battery positive electrode material of phosphotungstic acid (H3O 40 PW12 ·χH2O);

[0019] Step 7: weigh the phosphotungstic acid (H3O 40 PW 12 ·χH2O) was mixed with a weight of the synthesized nickel-rich ternary lithium-ion battery positive electrode material and then ground continuously for 30 min;

[0020] Step 8: Place the fully mixed materials into a tubular furnace and sinter at 300°C for 7 hours, then slowly cool down to room temperature at a certain rate to obtain the phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material.

[0021] Preferably, the sintering method in the fifth and eighth steps is a tubular furnace with an oxygen atmosphere.

[0022] Preferably, the grinding method in the second step and the fourth step is one or more of ball mill and manual grinding.

[0023] The beneficial effects of the phosphotungstic acid coated nickel-rich ternary lithium ion battery positive electrode material of the present invention are:

[0024] The positive electrode semi-motor made of the phosphotungstic acid-coated nickel-rich ternary lithium-ion battery positive electrode material of the present invention has significantly improved discharge capacity, good charge and discharge stability, and can effectively extend the battery life. The phosphotungstic acid-coated nickel-rich ternary lithium-ion battery positive electrode material of the present invention has low cost, significantly improved quality stability, significantly reduced heat generation rate and heat generation, and significantly delayed the time of the exothermic peak, so that the lithium-ion battery has excellent electrochemical performance while having good thermal safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0026] In the figure: Figure 1 The specific capacity cycle stability curve of the positive electrode half-cell prepared with the materials of Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention;

[0027] Figure 2 It is a comparison diagram of thermogravimetric analysis curves of positive electrode materials of Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention;

[0028] Figure 3 It is a comparison chart of thermal analysis DSC curves of the positive electrode materials of Example 1, Example 2, Example 3 and Comparative Example 1 in the present invention. DETAILED DESCRIPTION

[0029] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0030] The present invention provides a phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material, comprising a nickel-rich ternary lithium-ion battery positive electrode material and a material phosphotungstic acid (H3O 40 PW 12 ·χH2O), the positive electrode material of nickel-rich ternary lithium-ion battery is composed of nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 (OH)2) and a lithium source;

[0031] Preferably, the mass ratio of each component of the nickel-rich ternary lithium-ion battery positive electrode material is: nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 (OH)2): lithium source is 1:1.05;

[0032] Preferably, phosphotungstic acid (H3O 40 PW 12 ·χH2O) accounts for 0.5% to 2% of the mass of the positive electrode material of nickel-rich ternary lithium-ion batteries.

[0033] Preferably, the lithium source is selected from one of lithium hydroxide (LiOH·H2O) and lithium carbonate (Li2CO3).

[0034] Preferably, the nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 The particle size of (OH)2) is selected from one or more of 25 μm, 50 μm, 100 μm, 200 μm, 400 μm.

[0035] The present invention also provides a method for preparing a phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material, which specifically comprises the following steps:

[0036] Step 1: Weigh the nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 (OH)2) 10 parts and lithium source 10.5 parts;

[0037] Step 2: weigh the nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05Mn 0.05 (OH)2) and lithium source were mixed and ground for 30 min;

[0038] Step 3: Place the fully mixed materials into a tube furnace and sinter at 500°C for 5 hours with an oxygen flow rate of 50-150 ml / min;

[0039] Step 4: Take out the cooled powder and grind it for 5 minutes;

[0040] Step 5: Place the ground material into a tube furnace and sinter at 680-760°C for 15 hours to obtain a nickel-rich ternary lithium-ion battery positive electrode material;

[0041] Step 6: Weigh 0.5% to 2% of the mass of the synthesized nickel-rich ternary lithium-ion battery positive electrode material of phosphotungstic acid (H3O 40 PW 12 ·χH2O);

[0042] Step 7: weigh the phosphotungstic acid (H3O 40 PW 12 ·χH2O) was mixed with the synthesized nickel-rich ternary lithium-ion battery positive electrode material and then ground continuously for 30 minutes to obtain a mixed material;

[0043] Step 8: Place the fully mixed materials into a tubular furnace and sinter at 300° C. for 7 hours, and slowly cool to room temperature at a certain rate to obtain the phosphotungstic acid-coated nickel-rich ternary lithium-ion battery positive electrode material.

[0044] Embodiment 1:

[0045] Step 1: Weigh the nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 (OH)2) 10 parts and lithium source 10.5 parts;

[0046] Step 2: weigh the nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 After mixing (OH)2) and the lithium source, grinding is continued for 30 minutes to obtain a mixed material.

[0047] Step 3: Place the fully mixed materials into a tube furnace and sinter at 500°C for 5 hours with an oxygen flow rate of 50-150 ml / min;

[0048] Step 4: Take out the cooled powder and grind it for 5 minutes;

[0049] Step 5: Place the ground material into a tubular furnace and sinter at 680-760°C for 15 hours to obtain a nickel-rich ternary lithium-ion battery positive electrode material.

[0050] Step 6: Weigh 0.5% of the mass of the synthesized nickel-rich ternary lithium-ion battery positive electrode material of phosphotungstic acid (H3O 40 PW 12 ·χH2O);

[0051] Step 7: weigh the phosphotungstic acid (H3O 40 PW 12 ·χH2O) was mixed with the synthesized nickel-rich ternary lithium-ion battery positive electrode material and then ground continuously for 30 min.

[0052] Step 8: Place the fully mixed materials into a tubular furnace and sinter at 300°C for 7 hours, then slowly cool down to room temperature at a certain rate to obtain the phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material.

[0053] Embodiment 2:

[0054] Step 1: Weigh the nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 (OH)2) 10 parts and lithium source 10.5 parts;

[0055] Step 2: weigh the nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 (OH)2) and the lithium source are mixed and ground for 30 minutes to obtain a mixed material.

[0056] Step 3: Place the fully mixed materials into a tube furnace and sinter at 500°C for 5 hours with an oxygen flow rate of 50-150 ml / min;

[0057] Step 4: Take out the cooled powder and grind it for 5 minutes;

[0058] Step 5: Place the ground material into a tube furnace and sinter at 680-760°C for 15 hours to obtain a nickel-rich ternary lithium-ion battery positive electrode material;

[0059] Step 6: Weigh 1.0% of the mass of the synthesized nickel-rich ternary lithium-ion battery positive electrode material of phosphotungstic acid (H3O 40 PW 12 ·χH2O);

[0060] Step 7: weigh the phosphotungstic acid (H3O 40 PW 12 ·χH2O) was mixed with the synthesized nickel-rich ternary lithium-ion battery positive electrode material and then ground continuously for 30 min;

[0061] Step 8: Place the fully mixed materials into a tubular furnace and sinter at 300°C for 7 hours, then slowly cool down to room temperature at a certain rate to obtain the phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material.

[0062] Embodiment 3:

[0063] Step 1: Weigh the nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 (OH)2) 10 parts and lithium source 10.5 parts;

[0064] Step 2: weigh the nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 (OH)2) and a lithium source are mixed and ground for 30 min to obtain a mixed material;

[0065] Step 3: Place the fully mixed materials into a tube furnace and sinter at 500°C for 5 hours with an oxygen flow rate of 50-150 ml / min;

[0066] Step 4: Take out the cooled powder and grind it for 5 minutes;

[0067] Step 5: Place the ground material into a tubular furnace and sinter at 680-760°C for 15 hours to obtain a nickel-rich ternary lithium-ion battery positive electrode material.

[0068] Step 6: Weigh 2.0% of the mass of the synthesized nickel-rich ternary lithium-ion battery positive electrode material of phosphotungstic acid (H3O 40 PW 12 ·χH2O);

[0069] Step 7: weigh the phosphotungstic acid (H3O 40 PW 12 ·χH2O) was mixed with the synthesized nickel-rich ternary lithium-ion battery positive electrode material and then ground continuously for 30 min;

[0070] Step 8: Place the fully mixed materials into a tubular furnace and sinter at 300°C for 7 hours, then slowly cool down to room temperature at a certain rate to obtain the phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material.

[0071] Comparative Example 1:

[0072] Step 1: Weigh the nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 (OH)2) 10 parts and lithium source 10.5 parts;

[0073] Step 2: weigh the nickel cobalt manganese hydroxide precursor (Ni0.90 Co 0.05 Mn 0.05 (OH)2) and lithium source were mixed and ground for 30 h;

[0074] Step 3: Place the fully mixed materials into a tube furnace and sinter at 500°C for 5 hours with an oxygen flow rate of 50-150 ml / min;

[0075] Step 4: Take out the cooled powder and grind it for 5 minutes;

[0076] Step 5: Place the ground material into a tubular furnace and sinter at 680-760°C for 15 hours to obtain a nickel-rich ternary lithium-ion battery positive electrode material.

[0077] The materials of Example 1, Example 2, Example 3 and Comparative Example 1 were respectively prepared into positive electrode half-cells, and the specific steps were as follows:

[0078] The positive electrode material (positive electrode material prepared in Example 1, Example 2, Example 3, and Comparative Example 1), conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of positive electrode material: acetylene black: polyvinylidene fluoride = 8:1:1. After mixing, N-methylpyrrolidone (NMP) is added, and the mixture is stirred and mixed thoroughly to form a uniform positive electrode slurry, which is evenly coated on a 15 μm thick aluminum foil, and then dried in a blast drying oven at 120° C. for 12 h to obtain a positive electrode sheet for use.

[0079] The above-mentioned positive electrode sheet was used as the positive electrode, the metal lithium sheet was used as the negative electrode, Celgard 2500 was used as the separator (Celgard 2500 separator is a lithium-ion battery separator produced by Celgard Corporation of the United States), commercial electrolyte was added, and a button-type half-cell with a battery model of CR2032 (lithium manganese battery button cell model) was assembled in a glove box.

[0080] The battery cycle test steps are as follows:

[0081] The assembled button cell was left at room temperature (25°C) for 12 hours and then cycled, with a charge and discharge voltage of 2.8 to 4.3 V. The battery was first charged and discharged at a rate of 0.1C for three cycles, and after fully activating the electrode material, 50 cycles were performed at a rate of 0.2 to evaluate the battery's cycle performance.

[0082] The test procedure is: 0.1C constant current charge to 4.3V, then 4.3V constant voltage charge to current less than 0.05C, and then 0.1C discharge to 2.8V. After fully activating the electrode material, 0.2C charge and discharge for 50 cycles to evaluate the cycle stability of the battery. And calculate the capacity retention rate based on the 4th charge / discharge after 53 cycles. The calculation formula is as follows:

[0083] 53rd cycle capacity retention rate=(53rd cycle discharge capacity / 4th cycle discharge capacity)×100%.

[0084] Get data like Figure 1 As shown;

[0085] Table 1: Charge and discharge test results of Examples 1, 2, 3 and Comparative Example 1 of the present invention:

[0086]

[0087] The battery thermogravimetric test process is as follows:

[0088] After the cycle is completed, the battery is disassembled in the glove box, the positive electrode sheet is separated, and the positive electrode sheet is cleaned with dimethyl carbonate solvent to remove the residual electrolyte and left to dry. The positive electrode material is scraped off the aluminum sheet, 5 mg of the positive electrode material is weighed and placed in the sample cell, and a thermogravimetric experiment is performed on the thermal analyzer with a heating range of 30 to 330°C and a heating rate of 10.0°C / min. The mass change curve of the positive electrode material during the heating process is recorded. For comparison, thermogravimetric experiments were performed on different positive electrode material samples separately, and the data obtained are as follows Figure 2 shown.

[0089] Table 2: Thermogravimetric test results of batteries in Examples 1, 2, 3 and Comparative Example 1 of the present invention

[0090] project Quality retention rate (%) Example 1 93.59 Example 2 91.00 Example 3 89.47 Comparative Example 1 87.32

[0091] The battery thermal analysis test process is as follows:

[0092] The positive electrode material was obtained by the same pretreatment method as the thermogravimetric test. 2 mg of the positive electrode material was weighed and placed in the sample cell, and 1 mg of commercial electrolyte was added. The differential scanning calorimeter DSC experiment was performed on the thermal analyzer with a heating range of 30-330°C and a heating rate of 10.0°C / min. The heat generation curve of the positive electrode material during the heating process was recorded. For comparison, DSC experiments were performed on different positive electrode material samples separately, and the data obtained were as follows: Figure 3 As shown;

[0093] Table 3: DSC results of Examples 1, 2, 3 and Comparative Example 1 of the present invention

[0094] project Peak temperature(℃) Heat release (J / g) Example 1 228.74 72.90 Example 2 227.75 200.01 Example 3 238.85 251.08 Comparative Example 1 222.25 267.46

[0095] It can be seen from the data in Table 1 that the initial discharge capacity of the positive electrode half-cell made of the material of Example 1, the positive electrode half-cell made of the material of Example 2, and the positive electrode half-cell made of the material of Example 3 is significantly higher than that of the positive electrode half-cell made of the material of Comparative Example 1, indicating that the discharge capacity of the positive electrode half-cell made of the phosphotungstic acid-coated nickel-rich ternary lithium-ion battery positive electrode material is significantly improved. And the initial discharge capacity of the positive electrode half-cell made of the material of Example 1 is significantly higher than that of the positive electrode half-cell made of the material of Example 2 and the positive electrode half-cell made of the material of Example 3, indicating that when phosphotungstic acid (H3O) accounting for 0.5% of the mass of the synthesized nickel-rich ternary lithium-ion battery positive electrode material is taken 40 PW 12 ·χH2O), the positive electrode half-cell made of the phosphotungstic acid-coated nickel-rich ternary lithium-ion battery positive electrode material has the best initial capacity.

[0096] Compared with Comparative Example 1, Example 1 shows that compared with the positive electrode half-cell made of the positive electrode material not coated with phosphotungstic acid, the specific capacity of the positive electrode half-cell made of the coated positive electrode material increases by 34.58 mA / g in the first cycle, which significantly improves the electrochemical performance of the positive electrode half-cell made of the phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material between the voltage of 2.8 and 4.3 V. Compared with Comparative Example 1, Example 2 shows that the capacity retention rate is increased by 3.81%.

[0097] After 53 cycles of charge / discharge, the positive electrode half-cell made of the material of Example 1, the positive electrode half-cell made of the material of Example 2, and the positive electrode half-cell made of the material of Example 3 have a significantly higher capacity retention rate than the comparative example 1. It can be seen that the positive electrode half-cell made of the phosphotungstic acid-coated nickel-rich ternary lithium-ion battery positive electrode material has good charge and discharge stability and can effectively extend the battery life. And the capacity retention rate of the positive electrode half-cell made of the material of Example 2 is significantly higher than that of the positive electrode half-cell made of the material of Example 1 and the positive electrode half-cell made of the material of Example 3, indicating that when phosphotungstic acid (H3O) accounting for 1% of the mass of the synthesized nickel-rich ternary lithium-ion battery positive electrode material is taken, the positive electrode half-cell can be effectively extended. 40 PW 12 ·χH2O), the positive electrode half-cell made of the phosphotungstic acid-coated nickel-rich ternary lithium-ion battery positive electrode material has the best capacity retention rate.

[0098] It can be seen from the data in Table 2 that the quality retention rate of the positive electrode material of Example 1, the positive electrode material of Example 2, and the positive electrode material of Example 3 in the same temperature range is significantly higher than that of the positive electrode material of Comparative Example 1, indicating that the quality stability of the phosphotungstic acid-coated nickel-rich ternary lithium-ion battery positive electrode material is significantly improved, while the positive electrode material of Comparative Example 1 exhibits extremely strong structural instability, which is very unfavorable for maintaining the overall safety of the battery. The quality retention rate of the positive electrode material of Example 1 in the same temperature range is significantly higher than that of the positive electrode material of Example 2 and the positive electrode material of Example 3, indicating that when phosphotungstic acid (H3O) accounting for 0.5% of the mass of the synthesized nickel-rich ternary lithium-ion battery positive electrode material is taken, the quality stability of the phosphotungstic acid-coated nickel-rich ternary lithium-ion battery positive electrode material is significantly improved, while the positive electrode material of Comparative Example 1 exhibits extremely strong structural instability, which is very unfavorable for maintaining the overall safety of the battery. 40 PW 12 ·χH2O), the quality stability of the phosphotungstic acid-coated nickel-rich ternary lithium-ion battery positive electrode material is relatively high.

[0099] Compared with Example 1 and Comparative Example 1, the thermal weight loss rate of the coated positive electrode material is reduced by up to 6.27%, and the heat release is reduced by 194.56 J / g compared with the uncoated positive electrode material.

[0100] It can be seen from the data in Table 3 that the heat generation rate and heat generation of the positive electrode material of Example 1, the positive electrode material of Example 2, and the positive electrode material of Example 3 are significantly lower than those of the positive electrode material of Comparative Example 1, indicating that the heat generation rate and heat generation of the phosphotungstic acid-coated nickel-rich ternary lithium-ion battery positive electrode material are significantly reduced, and the initiation reaction of battery thermal runaway can be effectively controlled. The heat generation rate and heat generation of the positive electrode material of Example 1 in the same temperature range are significantly lower than those of the positive electrode material of Example 2 and the positive electrode material of Example 3, indicating that when phosphotungstic acid (H3O) accounting for 0.5% of the mass of the synthesized nickel-rich ternary lithium-ion battery positive electrode material is taken, the heat generation rate and heat generation of the positive electrode material of Example 1 are significantly lower than those of the positive electrode material of Example 2 and the positive electrode material of Example 3, indicating that when phosphotungstic acid (H3O 40 PW 12 ·χH2O), the heat generation rate and heat generation of the positive electrode material of the nickel-rich ternary lithium-ion battery positive electrode coated with the phosphotungstic acid are the lowest.

[0101] Depend on Figure 3 It can be seen that the time of the exothermic peak of the positive electrode material of Example 1, the positive electrode material of Example 2, and the positive electrode material of Example 3 is significantly delayed than that of the positive electrode material of Comparative Example 1, indicating that the thermal stability of the phosphotungstic acid-coated nickel-rich ternary lithium-ion battery positive electrode material is significantly improved. The exothermic peak of the positive electrode material of Example 1 in the same temperature range is significantly delayed than that of the positive electrode material of Example 2 and the positive electrode material of Example 3, indicating that when phosphotungstic acid (H3O) accounting for 0.5% of the mass of the synthesized nickel-rich ternary lithium-ion battery positive electrode material is taken 40 PW 12 ·χH2O), the phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material has the best thermal stability.

[0102] In summary, the positive electrode half-cell made of the phosphotungstic acid-coated nickel-rich ternary lithium-ion battery positive electrode material of the present invention has significantly improved discharge capacity, good charge and discharge stability, and can effectively extend the battery life. The quality stability of the phosphotungstic acid-coated nickel-rich ternary lithium-ion battery positive electrode material of the present invention is significantly improved, the heat generation rate and heat generation are significantly reduced, and the time of the exothermic peak is significantly delayed, so that the lithium-ion battery has excellent electrochemical properties while having good thermal safety performance.

[0103] It can be seen that phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode materials can improve the thermal stability of the positive electrode materials themselves, increase the thermal decomposition reaction temperature of the positive electrode materials, and achieve the purpose of delaying the thermal runaway rate of the battery and improving the safety performance of the battery. Phosphotungstic acid can be used as a protective layer to isolate the interface side reactions, which not only enhances the lithium ion diffusion capacity inside the positive electrode structure, but also inhibits the adverse structural transformation of the material, and synergizes the effect of trace phosphate and tungsten element coating to form a high-quality stable protective layer structure on the surface of the material, protecting the structural integrity of the electrode material while inhibiting the occurrence of side reactions, improving the battery cycle performance and discharge performance,

[0104] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material, comprising a nickel-rich ternary lithium-ion battery positive electrode material and a material coated on its surface, phosphotungstic acid (H3O 40 PW 12 ·χH2O), the positive electrode material of nickel-rich ternary lithium-ion battery is composed of nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 (OH)2) and a lithium source.

2. The phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material according to claim 1, characterized in that: The mass ratio of each component of the nickel-rich ternary lithium-ion battery positive electrode material is: nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 (OH)2):lithium source is 1:1.

05.

3. The phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material according to claim 1, characterized in that: The phosphotungstic acid (H3O 40 PW 12 ·χH2O) accounts for 0.5% to 2% of the mass of the nickel-rich ternary lithium-ion battery positive electrode material.

4. The phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material according to claim 1, characterized in that: The lithium source is one of lithium hydroxide (LiOH·H2O) and lithium carbonate (Li2CO3).

5. The phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material according to claim 1, characterized in that: The nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 The particle size of (OH)2) is selected from one or more of 25 μm, 50 μm, 100 μm, 200 μm, 400 μm.

6. The method for preparing a phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material according to any one of claims 1 to 5, comprising the following steps: Step 1: Weigh the nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 (OH)2) 10 parts and lithium source 10.5 parts; Step 2: weigh the nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 (OH)2) and lithium source were mixed and ground for 30 min; Step 3: Place the fully mixed materials into a tube furnace and sinter at 500°C for 5 hours with an oxygen flow rate of 50-150 ml / min; Step 4: Take out the cooled powder and grind it for 5 minutes; Step 5: placing the ground material into a tube furnace and sintering at 680-760° C. for 15 hours to obtain the nickel-rich ternary lithium-ion battery positive electrode material; Step 6: Weigh 0.5% to 2% of the mass of the synthesized nickel-rich ternary lithium-ion battery positive electrode material of phosphotungstic acid (H3O 40 PW 12 ·χH2O); Step 7: weigh the phosphotungstic acid (H3O 40 PW 12 ·χH2O) was mixed with a weight of the synthesized nickel-rich ternary lithium-ion battery positive electrode material and then ground continuously for 30 min; Step 8: Place the fully mixed materials into a tubular furnace and sinter at 300° C. for 7 hours, and slowly cool to room temperature at a certain rate to obtain the phosphotungstic acid-coated nickel-rich ternary lithium-ion battery positive electrode material.

7. The phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material according to claim 6, characterized in that: The sintering method in the fifth and eighth steps is a tubular furnace with an oxygen atmosphere.

8. The phosphotungstic acid coated nickel-rich ternary lithium-ion battery positive electrode material according to claim 6, characterized in that: The grinding method in the second step and the fourth step is selected from one or more of ball mill and manual grinding.

Citation Information

Patent Citations

  • Multi-element coated modified monocrystalline ternary anode material and preparation method thereof

    CN110803720A

  • Preparation method of tungsten-coated and doped single-crystal nickel-rich ternary positive electrode material

    CN113903907A

  • Composite positive electrode material, preparation method thereof and lithium ion secondary battery comprising composite positive electrode material

    CN117976831A

  • Tungsten oxide layer coated high-nickel ternary positive electrode material and preparation method thereof

    CN118538881A